Suillus punctipes Singer, Farlowia 1945 - Palamarchuk, Marina A.; Kirillov, Dmitry V.; Shadrin, Dmitry M. (Zenodo, 2021)
Suillus punctipes (Peck) Singer, Farlowia 2 (2): 277 (1945) (Fig. 4 a, b) Pileus 30–80 mm in diam., convex, then expended, when young covered by tufts of brown tomentum, soon becoming glabrous, sticky, bright yellow-brown, brownish-yellow, ochraceous-orange, fulvous. Hymenophore as tubes, adnate or slightly decurrent, very thin, 4–6 mm in width, brown, gray-brown, then dirty-brown-yellow or brownish-yellow. The hymenophore of young specimens exuding white droplets when fresh. Stipe 50–100 × 15 mm, cylindrical to clavate, yellow-brown, light ochraceous-orange, all covered with round, sticky glandular dots. The glandular dots on the stem remain white for a long time, only browning when bruised and in old specimens. Flesh white in pileus, pale orange in stipe; taste not distinctive. Smell fragrant, tarry and strong. Basidia 16–25 × 5–7.5 μm, clavate, 2- and 4-spores. Basidiospores (7)7.5–10 × 3–3.5 μm, Q = 2–3, fusiformellipsoidal, yellowish-brown. Cystidia (cheilo-, pleuro- and caulocystidia) 30–70 × 6.5–10 μm, clavate or fusiform, hyaline or with dark-brown content. Pileipellis consisting of parallel or slightly diverging pale yellowish-brown hyphae 5–8 μm diam., immersed in gelatinous substance. Clamp connections absent in all tissues. Ecology and distribution . The species is widely distributed in North America, where it forms ectomycorrhizae with Pinus strobus (Smith & Thiers 1964; Roody 2003). In Russia, it was found in Baikal region (Nezdojminogo 1969; Petrov 1991; Gorbunova & Stepanova 2015), Magadan (Vassilkov 1971; Sazanova 2009), Primorsky Kray (Vasilyeva 1973), Altai (Kovalenko1992), Northern Urals (Perevedentseva 2008), and West Siberia (Zvyagina 2008). It is believed that the species forms ectomycorrhizae with Pinus sibirica and P. pumila . Collection examined . RUSSIA, Troitsko-Pechorsky district, Pechoro-Ilychsky Nature Reserve, 12 km upstream the Pechora River from settlement Yaksha, 61°47’30.0”N, 57°04’18.0”E, green moss pine forest with Pinus sibirica , 18 Aug. 2000, col. M. Palamarchuk , ...